Realidad actual de personas con capacidades especiales del cantón piñas de la provincia de el oro, en el periodo enero-julio 2015 y la intervención del trabajador social - Ramírez Romero, Aída del Carmen (2016)
The lack of job opportunities to people with special needs has become a major problem, factors such as social prejudice, ignorance and mistrust have directly influenced so that these people have not been inserted in the workplace, it is why through research it has determined a low labor inclusion to this vulnerable group. With the completion of this research allowed to know about the current reality of people with different abilities Piñas Canton, also it refers to the most outstanding objectives of the Social Worker. the lack of services job placement, lack of employment opportunities, the highest level of education is primary, little knowledge: In the course of investigating the causes that do not allow the employment of people with special abilities such as determined the law of labor inclusion. In the process of labor inclusion involved several people such as family members of people with special needs, who are the direct motivators authorities, social workers then provide those seeking change, social cohesion and social justice are. It is for these reasons it is necessary to know from a social perspective thought both people with disabilities and family and society in general, and more delimitadamente at the work place, making it clear that my motivation to carry out this investigation, it is because in the profession of social work alternatives are sought to generate better days our society. In this area the Social Work as a mobilizer of knowledge is the great task to actively participate in social everydayness, build proposals for intervention and run involving a wide dissemination of legal aspects covered by the Constitution of the Republic of Ecuador and other documents, arranging compliance with laws and therefore the inclusion of people who clearly highlight this need, the awareness being necessary for active participation, without our actions as Social Workers will not have the desired success. This research has met the objectives where the need to give the possibility to-work personnel who conduct made visible are excluded by traditional patterns of disabilities that prevent invisibly people access, adding to this nondisclosure laws that cover, making it an unknown field.